脑机接口技术在脑卒中病人认知功能 康复中应用的范围综述. - 刘圆圆; 董琪; 闫雅丽; 姚嘉欣; 庞萌; 许娟 (Chinese Nursing Research, 2026)
Objective: A scoping review was conducted on relevant studies regarding the use of brain computer interface technology to promote the rehabilitation of Cognitive Function in stroke patients, aiming to identify brain computer interface technology intervention programs,outcome measures,and therapeutic effects,so as to provide references for future research. Methods:Relevant studies in CBM, WanFang Database, VIP Database, CNKI, Cochrane Library, PubMed, EMbase, Web of Science, MedLine Chinese and English databases Chinese and English databases were searched. The retrieval time was from establishment of databases to November 1, 2025. Literature were screened, extracted, and summarized based on inclusion and exclusion criteria. Data extraction and meta-analysis were performed on the included literature. Results: A total of 15 studies were included. Brain computer interface technology mainly included brain computer interface with functional electrical stimulation, exoskeleton robot and P300 spellers. The frequency of exercise were mostly 3-5 times per week,with the duration of a single training session mostly 30 minutes and the intervention cycle were 4 weeks. The outcome indicators involved three aspects:cognitive function,quality of life and safety. Conclusions:Brain computer interface technology could effectively improve cognitive function in stroke patients and enhance their abilities in daily living. However, related research is still in the exploratory stage. Future studies may focus on multidisciplinary collaboration to conduct large - sample, multicenter, long - term follow-up clinical trials,offering personalized intervention programs for patients with varying functional levels and promoting the usability and widespread application of brain computer interface technology in cognitive rehabilitation for stroke.